FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR PETANI SEKTOR TANAMAN PANGAN DI NUSA TENGGARA TIMUR - Johny A. Koylal; Stefanus M. Kuang; Jemseng C. Abineno (Partner, 2023)
One approach to measuring farmers' welfare is the farmer's exchange rate. The study aims to examine the development of exchange rates of farmers in the food crop sector with quantitative descriptiveness and the factors that influence it with multiple regression models. The results showed that from January 2017 to December 2020, the exchange rate of farmers in the food crop sector experienced a downward trend. Household consumption expenditure; price of seedlings; prices of medicines and feed; land rent, taxes, and others; transportation costs; the cost of adding capital goods; and the wages of farmworkers together are significant explanations of the exchange rate of farmers in the food crop sector. Meanwhile, partially, only the price of seeds has a significant effect on the exchange rate of farmers in the food crop sector. Key Words: farmer exchange rate, food crops, East Nusa Tenggara